2014
DOI: 10.1371/journal.pone.0103065
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis of Non-Union, Re-Operation, Infection, and Approach Related Complications after Anterior Odontoid Screw Fixation

Abstract: BackgroundAnterior odontoid screw fixation (AOSF) has been one of the most popular treatments for odontoid fractures. However, the true efficacy of AOSF remains unclear. In this study, we aimed to provide the pooled rates of non-union, reoperation, infection, and approach related complications after AOSF for odontoid fractures.MethodsWe searched studies that discussed complications after AOSF for type II or type III odontoid fractures. A proportion meta-analysis was done and potential sources of heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
(97 reference statements)
1
30
0
Order By: Relevance
“…In developing countries like ours, despite these intra-operative aids, the procedure can still be performed using pre-operative images and pertaining to our basic anatomical knowledge. Our results are comparable to previously published studies 10 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In developing countries like ours, despite these intra-operative aids, the procedure can still be performed using pre-operative images and pertaining to our basic anatomical knowledge. Our results are comparable to previously published studies 10 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, anterior approach is not justified in scenarios such as associated transverse ligament disruption, comminuted and significantly displaced fracture segments as well as posterior element injuries 19 . There is also high incidence of non-union in age groups of above 70 years with concomitant osteoporosis 20 . Posterior fusion is rather a more valid approach in such cases 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A CT was performed only in cases of clinical or radiological suspicion of non-union. Tian et al [26] observed that the pooled non-union rate based on CT scan was higher than that based on only X-rays. However, this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, it is important to note that many studies or reviews in the literature consist of rather small samples or small original study populations [8,26,30,31]. To the best of our knowledge, this series represents the largest study investigating mortality in patients aged 70 years and older with type II odontoid fractures treated with TAFOF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation